2014
DOI: 10.1016/j.dcn.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial working memory in very preterm and term born children—Impact of age and performance

Abstract: Working memory is crucial for meeting the challenges of daily life and performing academic tasks, such as reading or arithmetic. Very preterm born children are at risk of low working memory capacity. The aim of this study was to examine the visuospatial working memory network of school-aged preterm children and to determine the effect of age and performance on the neural working memory network. Working memory was assessed in 41 very preterm born children and 36 term born controls (aged 7-12 years) using functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
4
41
0
1
Order By: Relevance
“…Omizzolo et al (2013) showed that 7-year-old very preterm children were impaired in comparison to controls in different visuospatial tasks like block recall or dot locations. However, other studies revealed that very preterm and controls did not differ behaviorally in two visuospatial working memory tasks (Mürner-Lavanchy et al, 2014;Taylor, Donner, & Pang, 2011). It is important to stress that abilities required for accurately solving visuospatial and spatial orientation tests differ.…”
Section: Discussionmentioning
confidence: 97%
“…Omizzolo et al (2013) showed that 7-year-old very preterm children were impaired in comparison to controls in different visuospatial tasks like block recall or dot locations. However, other studies revealed that very preterm and controls did not differ behaviorally in two visuospatial working memory tasks (Mürner-Lavanchy et al, 2014;Taylor, Donner, & Pang, 2011). It is important to stress that abilities required for accurately solving visuospatial and spatial orientation tests differ.…”
Section: Discussionmentioning
confidence: 97%
“…In adults, a network of prefrontal, parietal, and anterior cingulate regions is reliably activated in working memory contexts (D'Ardenne et al, 2012;Todd & Marois, 2004;Osaka et al, 2003;Courtney et al, 1998;D'Esposito et al, 1995;Jonides et al, 1993), and activation in these regions increases with increasing working memory load (Rypma, Prabhakaran, Desmond, Glover, & Gabrieli, 1999;Barch et al, 1997;Braver et al, 1997). In children and adolescents, many studies find activation in similar frontoparietal and cingulate networks (Mürner-Lavanchy et al, 2014;Spencer-Smith et al, 2013;Geier, Garver, Terwilliger, & Luna, 2009;Tsujii, Yamamoto, Masuda, & Watanabe, 2009;Ciesielski, Lesnik, Savoy, Grant, & Ahlfors, 2006;Klingberg, 2006). Despite these similarities, there are also important differences in patterns of activation across adults and children, and both the specific pattern and source of these differences are currently unresolved.…”
Section: Introductionmentioning
confidence: 88%
“…Preliminary evidence of a catch‐up of activation patterns comes from a study by Murner‐Lavanchy et al 46. who showed that VPT children (7–12y) may have increased activation in superior frontal cortex to compensate for persistent functional deficits in the adjacent middle frontal gyrus 46. The most recent, and to date the largest, fMRI working memory study of VPT individuals found no working memory deficits in adulthood 47.…”
Section: Working Memorymentioning
confidence: 99%